2010
DOI: 10.3109/13625181003782860
|View full text |Cite
|
Sign up to set email alerts
|

Release of copper and indomethacin from intrauterine devices immersed in simulated uterine fluid

Abstract: The surface area of the copper and the pH of the test medium modulate the in vitro release of cupric ions from Cu-IUDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…They were paired for comparison according to the device properties and the release of cupric ion was determined by flame atomic absorption spectrometer for about 160 days. Consistent with the in vivo studies, copper release was higher during the first month, followed by a slower steady rate (Zhou et al., 2010 ; Zhang et al., 2015 ). Another recent study reporting on copper IUD corrosion (Cu 2 O), measured by X‐ray diffraction was focused on the benefit of intended use but neither copper release nor systemic exposure was considered (Wildemeersch et al., 2014 ).…”
Section: Assessmentsupporting
confidence: 79%
“…They were paired for comparison according to the device properties and the release of cupric ion was determined by flame atomic absorption spectrometer for about 160 days. Consistent with the in vivo studies, copper release was higher during the first month, followed by a slower steady rate (Zhou et al., 2010 ; Zhang et al., 2015 ). Another recent study reporting on copper IUD corrosion (Cu 2 O), measured by X‐ray diffraction was focused on the benefit of intended use but neither copper release nor systemic exposure was considered (Wildemeersch et al., 2014 ).…”
Section: Assessmentsupporting
confidence: 79%
“…The simulated uterine cavity fluid (g L −1 ) was prepared according to the ratio in Table 1 and stored for later use at 2–8 °C. 22…”
Section: Methodsmentioning
confidence: 99%
“…A number of additional authors reported the use of SUFs in studying copper, zinc, or indometacin release from IUDs (40)(41)(42)(43)(44)(45)(46)(47). However, in all of these studies, the media designed by Zhang et al (35) or the slightly modified version reported by Mora et al (39) were applied.…”
Section: Media Simulating Human Uterine Fluidmentioning
confidence: 99%